Perinatal depression in migrant and refugee women on the Thai–Myanmar border: does social support matter? - Fellmeth, G; Plugge, E; Fazel, M; Nosten, S; Oo, MM; Pimanpanarak, M; Phichitpadungtham, Y; Fitzpatrick, R; McGready, R (Royal Society, 2021)
Migrant and refugee women are at risk of perinatal depression due to stressors experienced before, during and after migration. This study assesses the associations between social support and perinatal depression among migrant and refugee women on the Thai–Myanmar border. We conducted a cohort study of pregnant and post-partum women. Depression status was assessed using a structured clinical interview. Received support, perceived support and partner support were measured in the third trimester. Logistic regression was used to calculate associations between social support measures and perinatal depression controlling for demographic, socio-economic, migration, obstetric and psychosocial factors. Four hundred and fifty-one women (233 migrants; 218 refugees) were included. The prevalence of perinatal depression was 38.6% in migrants and 47.3% in refugees. Migrants had higher levels of received, perceived and partner support than refugees. After controlling for all other variables, higher levels of received support remained significantly associated with a lower likelihood of perinatal depression in migrants (adjusted odds ratio 0.82; 95% CI 0.68–0.99). In both groups, depression history and trauma were strongly associated with perinatal depression. Our study highlights the importance of received social support to perinatal depression in migrant women on the Thailand–Myanmar border. The perinatal period offers a valuable opportunity to ask women about their support and offer community-level or public policy interventions to nurture support networks in current locations and resettlement destinations.